Die negativen Auswirkungen des krisenbezogenen Handelsprotektionismus auf die Schweizer Aussenwirtschaft - Simon J. Evenett; Johannes Fritz (Aussenwirtschaft, 2011)
– As a small and open economy, Switzerland is not independent from developments in international trade policy.The present article analyses to what extent Swiss foreign commercial interests have been harmed by discriminatory implementedmeasures since November 2008. The strong geographic and sectorial concentration of Swiss trade explains the relatively small direct effects found in the data.By contrast, Swiss commercial interests face a considerably bigger challenge from indirect effects in the form of artificial competition in third countries.Targeted export subsidies could lead to additional pricing pressure for half of total Swiss exports by trade value.
Keywords: 330